A Mathematical Model for the Initial Interaction Stage Between a Radar System and a Target Using GERT Network - Semenov, Serhii; Krupska-Klimczak, Magdalena; Mieczkowski, Patryk; Tarasenko, Yevhen; Voronets, Vitalii; Voronets, Oleksandr; Breslavets, Vitalii; Davydov, Viacheslav (MDPI, 2025)
The article presents a mathematical model of radar systems operating unde jamming conditions. The relevance of the study is highlighted by two main factors: the need to enhance the accuracy of radar systems and the requirement to incorporate new jamming factors into models, which raises challenges in maintaining the reliability of mathematical formalizations. Various modeling approaches, including Markov models, deep learning, and probabilistic filters, are analyzed. These methods enable radar systems to adapt to changing conditions and improve target detection, which are crucial for their effective operation under uncertainty. The article emphasizes the importance of integrating different techniques to develop algorithms capable of functioning in complex jamming environments. A key aspect of the model is its consideration of time delays and probabilistic characteristics, which help to formalize and optimize the system’s performance in variousbased on the Graphical Evaluation and Review Technique(GERT) network, offering in-depth analysis and adaptation of radar systems to changing conditions. This approach is a critical component for enhancing the resilience of radar systems in complex and uncertain operational environments.
Keywords: radar systems; mathematical modeling; target tracking; GERT networks